The Relationship Among Hypertension History, Maternal Age, Parity and Family Support with the Independence in Preventing Pre-Eclampsia - Umamah, Faridah; Santoso, Budi; Yunitasari, Esty; Anggraini, Fitri Dwi; Afridah, Wiwik (International Journal of Psychosocial Rehabilitation, 2020)
Preeclampsia is a medical problem that often occurs during pregnancy and is a leading cause of maternal death worldwide and in Indonesia; therefore, a discussion is important to help pregnant mothers be able to do self-care and maintain health as well as to recognize the danger signs of pregnancy to prevent and control preeclampsia. The research design used a cross-sectional approach. The population study was made up of 148 pregnant women, a large sample of 124 respondents was taken using simple random sampling. The independent variables were a history of hypertension, maternal age, parity, and family support while the dependent variable was independence in preventing preeclampsia. The instruments used were questionnaires and observation sheets. Data were analyzed bivariately with Pearson correlation and using multivariate with multiple linear regression analysis with significant level (α = 0.05).There were significant correlations between a history of hypertension (p=0.000, r=0.592), parity (p=0.000, r=0.752) and family support (p=0.000, r =0.810) with independence in preventing preeclampsia. There was no correlation between maternal age and independence (p=0.375, r=-0.101). Maternal age and history of hypertension together correlated with maternal independence in preventing preeclampsia. Health workers are expected to be able to increase their ability to prevent and detect preeclampsia for all pregnant women and families so that the incidence of preeclampsia and maternal and fetal mortality can be reduced.